2017
DOI: 10.1126/scisignal.aai9219
|View full text |Cite
|
Sign up to set email alerts
|

ERK signaling pathway regulates sleep duration through activity-induced gene expression during wakefulness

Abstract: Wakefulness is accompanied by experience-dependent synaptic plasticity and an increase in activity-regulated gene transcription. Wake-induced genes are certainly markers of neuronal activity and may also directly regulate the duration of and need for sleep. We stimulated murine cortical cultures with the neuromodulatory signals that are known to control wakefulness in the brain and found that norepinephrine alone or a mixture of these neuromodulators induced activity-regulated gene transcription. Pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 50 publications
5
67
0
Order By: Relevance
“…Phosphorylation was indicated to play a role also in Process S, as the loss of calcium/CaMKII gene resulted in significant reduction of sleep (Tatsuki et al, 2016). This finding is further supported by the observation that the wakefulness induced phosphorylation in the extracellular signal-regulated kinase (ERK) proteins, which are upstream of a group of genes expressed in activity-dependent manner and involved in sleep regulation (Mikhail et al, 2017). Moreover, the following phosphoproteomics studies revealed a number of genes in the intracellular signaling pathways change their states of phosphorylation along with the sleep/wake cycles (Diering et al, 2017;Wang et al, 2018;Bruning et al, 2019).…”
Section: Homeostatic Regulation Of Nrem Sleepmentioning
confidence: 76%
“…Phosphorylation was indicated to play a role also in Process S, as the loss of calcium/CaMKII gene resulted in significant reduction of sleep (Tatsuki et al, 2016). This finding is further supported by the observation that the wakefulness induced phosphorylation in the extracellular signal-regulated kinase (ERK) proteins, which are upstream of a group of genes expressed in activity-dependent manner and involved in sleep regulation (Mikhail et al, 2017). Moreover, the following phosphoproteomics studies revealed a number of genes in the intracellular signaling pathways change their states of phosphorylation along with the sleep/wake cycles (Diering et al, 2017;Wang et al, 2018;Bruning et al, 2019).…”
Section: Homeostatic Regulation Of Nrem Sleepmentioning
confidence: 76%
“…Conversely, large decreases in MAPK phosphorylation occur during SWA induced by sedative or anesthetic agents and during the homeostatic regulation of waking SWA (Kohtala et al, 2016(Kohtala et al, , 2019b. Intriguingly, the MAPK pathway has been shown to regulate sleep duration through activity-induced gene expression during wakefulness, with p44/42-MAPK deletion or inhibition significantly increasing the duration of wakefulness in mice (Mikhail et al, 2017). Though the function of this phenomenon remains almost completely unstudied, ENCORE-D suggests that the period dominated by waking SWA in response to rapid-acting antidepressants represents a physiologically meaningful step for the subacute consolidation of activity-induced synaptic changes, involving alterations in both protein synthesis and energy metabolism, resembling deep or local sleep.…”
Section: Sleep and Rapid Antidepressant Effectsmentioning
confidence: 99%
“…20-500 ng of mRNA was used to synthesize cDNA using iScript's cDNA Synthesis Kit (Bio-Rad), cDNA diluted 1:10 in RNAse-free H 2 O, and measured using a CFX96 Real-Time System. Primers were designed for these studies, with the exception of Homer1a, for which sequences were established in a prior study (Mikhail et al, 2017). Primer specificity was confirmed using NIH Primer Blast (see Table S1 for primer sequences).…”
Section: Quantitative Real-time Pcr (Qpcr) and Stability Analysismentioning
confidence: 99%